A Combined Regimen Study of WR 2721 and Sodium Nitrite for Protection against Cyanide Intoxication in Mice - Saini, S.K. (Asian Journal of Chemistry, 2010)
The antidotal action to cyanide poisoning by a combined regimenof sulphydryl compound WR 2721 and methemoglobin former,sodium nitrite was investigated in mice. The prophylaxis efficacyof the regimen was evaluated by administering candidate compoundsin different doses to mice challenged by 2 x LD50 of sodiumcyanide. A significant protection was observed against cyanidepoisoning at a combined dose of WR 2721 400 mg/kg andNaNO2 100 mg/kg. The individual candidates when injected ip. indifferent doses did not show much potential against cyanide toxicity.